An Analysis of project-based learning approaches in enhancing English proficiency among higher students - Alek Andika; Suhailah Binti Hussien; Atik Asroriyah; Dwi Heriyanto; Berlin Insan Pratiwi; Hastri Firharmawan; Zulfa Nabila (IRecall Journal, 2024)
This research delves into the impact of project-based learning approaches on improving English language proficiency among students. Focusing on relevant literature, the study delineates the role of practical projects in enhancing communication skills, motivation, and student engagement. The results of the literature analysis indicate that this approach provides an authentic learning context, facilitating holistic English language skills. Students involved in these projects show a significant improvement in speaking and writing abilities, concurrently boosting their motivation to learn. Furthermore, collaboration within projects enhances social skills and problem-solving abilities. The implications of this research contribute to the design of English language curricula in higher education, emphasizing the need to integrate project-based learning approaches.